2002
DOI: 10.1080/00223980209605545
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Animal Tracks: A Possible Cognitive Artifact of Human Evolution

Abstract: Although many human behaviors are held to have adaptive significance, specific examples of behaviors that represent direct holdovers from the ancient world have been few, particularly in the cognitive realm. In the present research, the authors tested the hypothesis that such cognitive examples might in fact exist and be experimentally verifiable. They suggested that human predispositions to learn basic aspects of hunting with relative ease might be "left over" from human evolution in the pre-agricultural past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…In our own work on relatively neglected areas of eyewitness testimony (memory for weapons and vehicles), recognition accuracy for handguns, seen only minutes previously, was consistently under 50% (Sharps et al 2003). Vehicle identification was even worse; a vehicle recognition memory task yielded only 25% accuracy on average (Villegas et al 2005), again for vehicles seen only minutes before.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In our own work on relatively neglected areas of eyewitness testimony (memory for weapons and vehicles), recognition accuracy for handguns, seen only minutes previously, was consistently under 50% (Sharps et al 2003). Vehicle identification was even worse; a vehicle recognition memory task yielded only 25% accuracy on average (Villegas et al 2005), again for vehicles seen only minutes before.…”
mentioning
confidence: 93%
“…Our recent studies (Sharps et al 2003;Villegas et al 2005) have built toward an understanding of memory for forensically-relevant inanimate objects such as weapons and vehicles, and toward a systematic understanding of eyewitness memory for person, object, and setting in context (Sharps et al 2007;Sharps and Hess 2008). This approach, with its emphasis on systematic variation of perpetrator, weapon, and surroundings, has allowed us to examine the kinds of errors made by eyewitnesses, and the relative prevalence of the different types of errors observed, with reference to controlled, systematically-varied contexts.…”
mentioning
confidence: 97%
“…As the interest in the effects of social influences on memory performance has increased, so has the interest in examining human memory from a functionalist perspective (see, e.g., Nairne, 2005;Sharps, Villegas, Nunes, & Barber, 2002). In one example of this line of inquiry, Nairne, Thompson, and Pandeirada (2007) tested a prediction that processing list items in terms of their survival value might benefit participants more than other wellestablished deep-processing manipulations.…”
mentioning
confidence: 99%
“…Both the Sharps et al (2002) article-despite some item-selection issues-and the work of Nairne et al (2007) demonstrated that empirical tests of a priori predictions that are based on a functionalist analysis of human memory are possible, and they can lead to fruitful avenues of investigation. In fact, both studies pointed to the conclusion that thinking about objects in terms of their prospective uses seems to be one of the best deep-processing tasks uncovered to date.…”
mentioning
confidence: 99%
“…These search strategies are also found in human wayfinding, both in determining the next move with respect to immediate surroundings, and in reviewing available resources from a situating overview such as a map. Seeking behaviours seem to come naturally to humans, possibly because they are similar to the foraging and hunting behaviours of our ancestors (Sharps et al 2002).…”
Section: Epistemic Principles: Building Knowledgementioning
confidence: 99%